(untitled) (Journal of the College of Basic Education, 2022)
(The two researchers) touched the problem of their research through a field study of elementary school schools, in which they observed how students organize the drawing board and distribute the elements within the space of this painting and how to link them to organizational relationships that can give the recipient a mental perception of the artistic expression of these students in organizing the space of the drawing board Accordingly, this problem was formulated by asking the following questions: 1- What is the level of artistic expression in the students ’drawings? 2- Are there differences in the level of artistic expression according to the gender variable? 3- Are there correlations between the fields of artistic expression and psychological adjustment? As the current research aims to identify the following: 1- The level of artistic expression in students ’drawings. 2- Differences in the level of artistic expression according to the gender variable. 3- Relationships between the fields of artistic expression and psychological conditioning. In carrying out this research, the two researchers used two tools: the student fee analysis form prepared by (Hassan, 2006) and the second for the psychological adjustment scale that he prepared (Gabriel, 1996). 1- The low level of artistic expression among students in late childhood, and for males and females alike. The most important recommendations are: - Paying attention to art education lessons in the late childhood stage, which is measured in the sixth primary stage. The most important proposals are: - The artistic expression of primary school students and its relationship to the self-concept.